Advancing Malaria Prevention and Control in Africa Through the Peace Corps-US President's Malaria Initiative Partnership - Susan J Henderson MD, MPH; Allison Belemvire MPH; Roman Nelson MBA; Anne Linn MPH; Leah F Moriarty MPH, PhD; Emma Brofsky MSPH; Mamadou Diaw PhD; David Gittelman MPH (SAGE Publishing, 2020)
Background Peace Corps is a US government volunteer service agency which provides trained Volunteers to assist host countries in addressing critical development challenges at the community level. The US President's Malaria Initiative provides technical expertise and financial resources to reduce malaria morbidity and mortality in focus countries in sub-Saharan Africa. Objective We aim to describe the nature of the collaboration between Peace Corps and President's Malaria Initiative (PMI) and highlight examples of the partnership in select countries. Methods We conducted an analysis of retrospective data obtained from Peace Corps and PMI for the years 2014-2019. Results Volunteers were able to learn about and work on malaria prevention and control with PMI in three key ways: a malaria-specific training program for staff and Volunteers; malaria-focused small grants; and extension of Volunteer assignments for a third year to support malaria projects. Successful Peace Corps projects supported by PMI, at the community level, were highlighted, with a focus on Rwanda, Benin, Zambia, Madagascar, and Senegal. In Fiscal Year 2019, 1408 Volunteers contributed to malaria prevention activities in 18 Peace Corps programs across Africa, of which 15 were PMI focus countries. While the majority of documented work by Volunteers has involved social and behavior change, there were many other ways to partner with PMI staff. Conclusion Each of the proven interventions that PMI supports for malaria prevention and control may have a role for Volunteer involvement. Combined with the technical expertise and the relationships that PMI staff have with national-level counterparts in PMI focus countries, the continued collaboration between Peace Corps and PMI can accelerate the fight against malaria.